Teachers and the Mapuche Historical-Educational Knowledge in the Teaching of History - Omar Turra-Díaz (Universidad Nacional, Costa Rica, 2015)
This paper presents the results of a research aimed at revealing the significance of the historical-educational Mapuche knowledge for teachers and its incorporation in the school history. The research subjects were teachers of History at secondary schools located in the province of Arauco, whose students are mostly of Mapuche-lafkenche territorial identity. The study was conducted from a qualitative methodology with a case study design, using the semi-structured interview technique for data collection and a phenomenological method for data analysis and concentration of meanings. The results demonstrate common significance in terms of the relevance of the Mapuche cultural knowledge within the school knowledge, the manifestation of a poor understanding of the Mapuche historical-educational knowledge, and the absence of a pedagogical work including this knowledge in the teaching of History. We conclude that even with the discourses of recognition and appreciation of cultural diversity and of indigenous cultural and educational rights, the school history, in the interethnic context, proposes and promotes a Eurocentric cultural knowledge that replicates the traditional pedagogical discourse of History.